Adaptive Scan-On-Receive Based on Spatial Spectral Estimation for High-Resolution Wide-Swath Synthetic Aperture Radar - Bordoni, F.; Younis, M.; Varona, E. Makhoul; Krieger, Gerhard (IEEE Geoscience and Remote Sensing Symposium (IGARSS), 2009)
Intensive research is currently ongoing in the field of Smart Multi-Aperture Radar Techniques (SMART) for high-resolution wide-swath Synthetic Aperture Radar (SAR) imaging. This work investigates the possibility of applying direction of arrival estimation methods to spaceborne SMART SAR systems, that employ receive beam steering. In particular, a new algorithm based on the actual spatial distribution of the received signal power is proposed. The performance of the algorithm is evaluated by Monte Carlo simulations and compared with that of the conventional scan-on-receive approach, in different operational scenarios. The Cramér Rao Lower Bound is also reported as a benchmark on the performance. ©2009 IEEE.
DLR Import::2019-04-03
Keywords: SAR; SCORE; SMART